Elucidating law - Dickson, Julie (Oxford legal philosophy, 2022)
In Elucidating Law, Julie Dickson addresses questions concerning the methodology of legal philosophy and advocates that legal philosophers should espouse an 'Indirectly Evaluative Legal Philosophy'. This approach can facilitate legal philosophers' understanding of aspects of the nature of law, without regarding law as inherently morally valuable.